Effect of depression before breast cancer diagnosis on mortality among postmenopausal women - Liang, Xiaoyun (Cancer, 2017)
CONDENSED ABSTRACT: Women with newly developed depression before the diagnosis of breast cancer had a modestly but significantly increased risk for death from any cause and death from breast cancer if diagnosed at late stage. The results also highlight the importance of prevention efforts to support mental health and prevent initial emergence of depression among older women. BACKGROUND: Few previous studies investigating depression before breast cancer diagnosis and breast cancer specific mortality have examined depression measured at more than one time point. This study aims to investigate the effect of depression (combining depressive symptoms alone and with antidepressant use) measured at two time points before breast cancer diagnosis on all-cause mortality and breast cancer-specific mortality among older postmenopausal women. METHODS: A large prospective cohort, the Women's Health Initiative (WHI), was used. The study included 3095 women with incident breast cancer who had measures of depressive symptoms and antidepressant use before diagnosis at baseline and at Year three. Multivariable Cox proportional hazards regression was used to estimate adjusted hazard ratios between depression at baseline, depression at Year three, and combinations of depression at these time points, and all-cause mortality and breast cancer-specific mortality. RESULTS: Depression at Year three before breast cancer diagnosis was associated with higher all-cause mortality after adjusting for multiple covariates (HR, 1.35; 95% CI, 1.02-1.78). There was no statistically significant association of baseline depression and all-cause mortality or breast cancer-specific mortality, whether or not depression was also present at Year three. In women with late-stage (regional or distant stage) breast cancer newly developed depression at Year three was significantly associated with both all-cause mortality (HR, 2.00; 95% CI, 1.13-3.56) and breast cancer specific mortality (HR, 2.42; 95% CI, 1.24-4.70). CONCLUSIONS: Women with newly developed depression before the diagnosis of breast cancer had a modestly but significantly increased risk for death from any cause and death from breast cancer in late stage.